Assessment of Mitral Regurgitation Severity by Doppler Color Flow Mapping of the Vena Contracta in Dogs. (16th June 2014) - Di Marcello, M.; Terzo, E.; Locatelli, C.; Palermo, V.; Sala, E.; Dall'Aglio, E.; Bussadori, C.M.; Spalla, I.; Brambilla, P.G.
<x xml:space="preserve">Abstract</x> Background Quantitative and semiquantitative methods have been proposed for the assessment of MR severity, and though all are associated with limitations. Measurement of vena contracta width (VCW) has been used in clinical practice. Objective To measure the VCW in dogs with different levels of MR severity. Animals Two hundred and seventy‐nine dogs were classified according to 5 levels of MR severity. Methods This was a retrospective study. EROA and regurgitant volume calculated by the PISA method, were measured and indexed to BSA. Descriptive statistics were calculated for VCW and VCW index for all categories of MR severity. Spearman's rank correlation coefficients (ρs) were calculated to compare the results of the different methods (VCW and VCW index vs RV PISA, RV PISA index, EROA, EROA index), and between VCW and VCW index versus MR severity. Results All Spearman's rank correlation coefficients were significant (P < .001). The median values of VCW resulted of 2.9 mm (IQR 3.4–2.5) and of 4.6 mm (IQR 5.4–4.1) in the groups previously classified as mild‐to‐moderate and moderate‐to‐severe, respectively. The median values of VCW index resulted of 4.4 mm/m2 (IQR = 5.5–4.2) in mild‐to‐moderate MR and of 10.8 mm/m2 (IQR = 12.8–9.4) in moderate‐to‐severe MR. Conclusion and Clinical Importance This is not a validation study against any previously validated invasive gold standard, the VCW method has proved easy to employ and it might be an additional tool in quantifying disease severity that supports, rather than replace, data coming from other techniques in daily clinical practice and research.